Pemberdayaan Masyarakat Dalam Pemberian MP ASI Terhadap Terjadinya Konstipasi Pada Bayi di Kelurahan Baru Ladang Bambu Kecamatan Medan Tuntungan - Rizky Andriani Bakara; Emelia Apriani Tampubolon (Journal of Community Development, 2022)
The Ministry of Health (2019) revealed that on average, 401 newborns in Indonesia die before they are one year old. The data comes from the government's latest survey, the 2020 Indonesian Demographic Health Survey (SDKI). Based on BPS data (2020), the under-five mortality rate per 1000 live births according to the age of the mother at delivery in 2017 was mostly at the age of 40-49 years (58%) and at the age of <20 years (40%). The prevalence of constipation in Indonesia is very small, in Bali in children aged 4-6 years the prevalence of constipation is 15.1%, while in children in Padang Barat Subdistrict, Padang City the constipation rate is 19.9 & with a ratio between males and females is 1.2: 1Constipation is a condition where feces harden so that it is difficult to pass through the anus, and causes a disturbed or uncomfortable feeling in the rectum. Contipation occurs at all ages, and is generally characterized by a low frequency of bowel movements (less than 3 times a week). Breastfed infants may have a bowel movement after every feeding or only once in 7-10 days (Eka, 2014). Constipation may occur due to early complementary feeding. The optimal age for starting solids is 6 months old. The recommendation for complementary feeding can be started when the baby is 4-6 months old. Exclusive breastfeeding for 6 months provides many benefits for the baby and also the mother.